Why Is the supervision of 3-kilogram LPG in Banggai Still Ineffective - Djohanis, Herni; Lestari, Sri; Supadiyasa, I Wayan (Public Policy Journal, 2025)
The supervision of 3-kilogram Liquefied Petroleum Gas (LPG) distribution in Banggai Regency remains problematic, particularly in achieving equitable access and effective regulatory enforcement. This study aims to analyze the implementation of supervision policies and identify factors affecting their effectiveness. Using a qualitative descriptive approach, seven key informants were selected through purposive sampling. Data were collected through in-depth interviews, field observation, and document analysis, and examined using Miles, Huberman, and Saldana’s interactive model. The findings reveal that several policy implementation indicators—such as communication between stakeholders, the availability of supervisory personnel, access to information, and bureaucratic coordination—are still suboptimal. These issues reflect broader national challenges in distributing subsidized LPG, a critical energy source for low-income households and micro-enterprises in Indonesia. The study highlights the need for better policy communication, increased supervisory capacity, clearer Standard Operating Procedures (SOPs), and stronger coordination among government agencies and PT Pertamina. In addition, innovative, technology-based monitoring tools such as app-based reporting systems are recommended to improve transparency and accountability. These recommendations not only address local weaknesses in Banggai Regency but also provide insights applicable to other regions with similar challenges. Strengthening policy implementation at the regional level is key to improving the distribution of subsidized energy nationwide.